Darwin's Cathedral, Bowlby's Cloister: The Use of Attachment Theory for the Studies in Medieval Religion, with the Example of The Book of Margery Kempe - Dresvina, Juliana (Irish theological quarterly, 2020)
The article considers whether religion in general can be viewed as adaptation and if medieval Catholicism in particular can be seen as a reflection of the human necessity to be emotionally attached to a primary caregiver, especially in the early stages of people's lives. It observes that in a period of high instability and often regressive child-rearing practices, God and/or a special saint could represent a stable and adequate attachment figure, facilitating relationships which contributed to mental well-being of the devotees. The article also suggests that, due to historic circumstances, the proportion of insecure attachment was probably higher among medieval populace than among modern people, and traces the evidence of such attachment style in The Book of Margery Kempe (late 1430s), arguably the first vernacular biography in English.